Associative Field of Ethnonym-Stimulus ‘Teleuts’ in Ethnic Self-Identification Modeling of Bachat Teleuts - V. A. Kameneva; N. V. Rabkina; A. P. Kartavtseva (Научный диалог)
The ethnic component, represented in the linguistic consciousness of the teleuts, a small indigenous people living on the territory of the Kemerovo region — Kuzbass, is considered. The associative field, built on the basis of reactions to the ethnonymstimulus ‘teleuts’, was analyzed using partofspeech and attributive methods and the method of associative ethnic portraits proposed by T. A. Ershova. The data obtained supplement the available information of anthropologists, local historians and cultural scientists about the national selfconsciousness of the teleuts. It is proved that the teleuts have a positive ethnic identity. The dominant number of associates for the wordethnonym ‘teleuts’ have a complex of positive additional emotional, evaluative and expressive meanings. For the participants in the experiment, it turned out to be important commonality based on family kinship, reassessment of their ethnic group, the significance and uniqueness of which are the result of not only the presence of a developed system of original customs and traditions, but also its small number. The teleuts define themselves as a small indigenous people living on the territory of the Kemerovo region, whose representatives are carriers of a wide range of positive qualities and their own unique culture. Modeling of the ethnic selfidentification of the Bachat teleuts on the basis of a comparison of associative fields, actualized by the ethnonym and endoethnonyms, seems promising.